Effects of tidal wave modulation on coastal flooding along a tide-river context: Case of the seine estuary - EI Turki; J Deloffre; R Gilbert; ET Mendoza; E Salameh; N Abcha; N Lecoq; B Laignel (Annals of Marine Science - Peertechz Publications, 2023)
Tidal waves modulated over a range of timescales, from inter-daily to inter-annual variations, are responsible for coastal flooding which is enhanced in tide-river environments. The research described here investigates the tidal dynamics interacting with the fluvial component in the Seine estuary (NE France), an excellent natural laboratory for its time-varying flow and the available water-level records provided by tide gauges along the estuary. The tidal signal has been analyzed together with the river discharge during 25 years (1990-2015) in the Seine Bay, including the estuary and the marine tides at Cherbourg, by the use of a series of spectral and physical approaches.  The main results highlighted that the tidal modulation is basically induced by the time changes of the harmonic components of M2, S2, N2, and K2 with significant shifts in the middle of the estuary. The estuary takes a flood-dominant behavior when the deformation of tides increases in the river section during the period 1999-2002 with an interaction between the high variability of tidal range and the extreme river discharge. This opposite effect of the river and its resistance is enhanced under higher tidal flow velocity; which increases the water depth and reduces the hydraulic head and the tidal amplification factor in a low turbid estuary.  This work carried out in the framework of the SWOT 3MC research program, gives some insights into the complex behavior of tidal propagation in the Seine estuary and its non-stationary dynamics close to the river effects in response to extreme sea levels leading to coastal flooding.